Climate-Responsive Architecture: Optimizing Passive Cooling Strategies for Enhanced Thermal Comfort in the Design of University Senate Buildings - Abdullahi, Musa Khalifa; Sagada, Musa Lawal; Yakubu, Kashim Ibn; Tijjani, Zakari Abdullahi; Aule, Thomas Terna (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2025)
The rising demand for energy-efficient and thermally comfortable buildings in hot-dry regions underscores the need for climate-responsive architecture in Nigeria's institutional infrastructure. Despite global advances in passive design, many university senate buildings in northern Nigeria remain poorly optimised, resulting in excessive heat gain and high cooling energy demand. This study investigates the passive cooling performance of selected senate buildings to enhance thermal efficiency and environmental sustainability. Using building simulation software, wall, roof, and glazing configurations were analysed for thermal transmittance (U-values) and energy performance. The results revealed that incorporating polystyrene insulation, double glazing, and green roofing systems significantly reduced U-values and improved indoor thermal comfort compared to conventional designs. Findings affirm that design parameters such as material composition and envelope detailing directly influence building energy performance. The study emphasises the importance of integrating passive cooling strategies in institutional design to align with national and international energy efficiency standards. It concludes by recommending the adoption of simulation tools in design practice, capacity-building for designers, and policy reforms promoting low-carbon building envelopes. Future research should extend simulations to life-cycle analysis and real-time monitoring for broader regional applicability.